(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Untreated myopia is the leading cause of vision impairment in children. The study was conducted in order to determine the prevalence and some factors associated with myopia in secondary school students in Hoang Mai town, Nghe An province. Methods: The study employed descriptive analytical research method with the study subjects of secondary school students in Hoang Mai town, Nghe An province. Results: The prevalence of myopia in secondary school students in Hoang Mai town was 14.2%, in which grade 8 and grade 9 students were at a higher risk of myopia than grade 6 with OR = 1.7 (95%CI:1.2–2.5) and OR = 1.8 times (95%CI:1,2–2.6). Factors associated with myopia included near vision distance < 30 cm, with OR = 5.2, 95%CI: 3.5 – 7.9, p < 0.01; eye rest after 30 minutes of continuous near vision, with OR = 1.6, 95%CI: 1.1-2.5, p < 0.05; outdoor activity time < 14 hours/1 week (OR= 1.77, 95%CI: 1.15 – 3.9, p < 0.05) and reading and writing at home ≥ 21 hours/1 week ( OR = 1.5, 95% CI: 1.1- 2.1, p < 0.01). Conclusions: Near vision distance < 30 cm, continuous reading for 30 minutes without eye rest, outdoor activity time < 14 hours/week, and reading and writing > 21 hours/week were factors associated with myopia in the study subjects.